1989
DOI: 10.1128/jb.171.3.1278-1283.1989
|View full text |Cite
|
Sign up to set email alerts
|

The algR gene, which regulates mucoidy in Pseudomonas aeruginosa, belongs to a class of environmentally responsive genes

Abstract: The Pseudomonas aeruginosa capsule, composed of polysaccharide alginate, is an important Pseudomonas virulence factor encountered primarily in cystic fibrosis. The regulatory algR gene positively controls transcription of a key alginate biosynthetic gene, algD. The algR gene was subcloned and sequenced by creating a set of nested deletions in M13 bacteriophage. DNA sequence analysis of algR revealed the homology of its gene product with a recently recognized class of environmentally responsive bacterial regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
158
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(165 citation statements)
references
References 41 publications
7
158
0
Order By: Relevance
“…We therefore reproduced the mucoid phenotype in our P. aeruginosa strains by transformation with the multicopy vector pUCPKS containing algU (pUCPalgU). Under these conditions we confirmed that the algR mutant S39 is severely reduced in alginate production (Table 1), in agreement with previous studies in mucoid P. (19,32,34). However, under these conditions, the fimS mutant S62 still produces large amounts of alginate similar to the control (Table 1).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We therefore reproduced the mucoid phenotype in our P. aeruginosa strains by transformation with the multicopy vector pUCPKS containing algU (pUCPalgU). Under these conditions we confirmed that the algR mutant S39 is severely reduced in alginate production (Table 1), in agreement with previous studies in mucoid P. (19,32,34). However, under these conditions, the fimS mutant S62 still produces large amounts of alginate similar to the control (Table 1).…”
Section: Resultssupporting
confidence: 81%
“…As a consequence, studies on the regulation of alginate production have been carried out largely in variants selected for the stable expression of mucoidy (3,19,30,32). Such variants have been subsequently shown to contain mutations in the anti-sigma factors algN or mucA (which suppress the sigma factor AlgU) and thus result in upregulation of AlgU activity (2,3,33).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism for enhanced alg expression caused by Ca 2ϩ addition is not known. However, the results suggest that a Ca 2ϩ -controlled factor(s) may be involved in alg gene regulation, either through a previously identified regulator, such as one of the two-component sensory systems known to be involved in alg regulation (9,22,70), or through another regulatory factor that has not yet been identified. In biofilms, Ca 2ϩ may play an additional role in the observed increase in biofilm thickness by ionic cross-linking and gelling of the uronic acid residues, thereby modifying the biofilm architecture.…”
Section: Discussionmentioning
confidence: 54%
“…biosynthesis requires activation of the alternative sigma factor AlgU (12,13) and the two-component transcriptional regulator AlgR (12,14,15). Two-component signal transduction systems are important in regulating the bacterial response to environmental conditions.…”
mentioning
confidence: 99%